Namibian fairy circles: Hostile territory for soil nematodes - Amy Treonis; Andrew Bell; Eugene Marais; Gillian Maggs-Kölling (PLoS ONE, 2025)
Fairy circles are rings of grass (2–12 m diameter) with centers of bare soil that are found in some arid grasslands. Above- and belowground chemical and biological processes have been explored in an ongoing debate about the ultimate causes of this pattern. Belowground biota, including beneficial and pathogenic nematodes in the soil food web, may both influence and respond to the formation of fairy circles. For example, root-feeding nematodes have the potential to enhance plant water stress, promoting the spatial organization into rings to minimize competition. We studied the soil nematode communities associated with Stipagrostis fairy circles along a 900-km range in the Namib Desert of Namibia in southern Africa. Nematode abundance and diversity were highest in soils beneath the vegetation rings that define fairy circles and in soils in the vegetated matrix surrounding the rings, demonstrating the positive impact of plant-derived resources (i.e., roots and organic matter) on nematode communities. Network analysis of nematode communities showed that in many ring soils, fungal or root hair-feeding Aphelenchoides, Ditylenchus, and Hexatylus frequently co-occurred among other plant-parasitic taxa. In contrast, soils from the bare centers of fairy circles had lower organic matter content and were nearly defaunated. Fairy circle centers appear to be a hostile environment for soil nematodes, reflecting a resource-limited soil food web that may contribute to the persistent absence of vegetation. Bacterial-feeding Acrobeloides were over-represented in communities in the centers, which could reflect an association with termites or ants, whose activity has been proposed to play a role in fairy circle formation. These findings show that nematode communities respond to the unique environmental conditions created by fairy circles, and nematode assemblages found in center, ring, and matrix soils also may contribute to sustaining the pattern.